Thought and the Nature of Contemporary Islamic Philosophy - Siti Yani Yuliyani; Maspuroh; Helmi Muslimah (Penerbit Hellow Pustaka, 2025)
The essence of Islamic philosophy is a thought that comes from the teachings of Islam. Islamic philosophy is an Islamic teaching that fosters Muslims in forming character, personality, good morals and good behavior in accordance with the teachings of Islam and all the personalities that exist in a person inspire Islam itself. The purpose of Islamic philosophy is to create harmony in life, tranquility, peace and can help each other. This Islamic philosophy discusses the thoughts of Muslim figures and studies them to be applied in carrying out daily life, starting from thought patterns, behavior and development in a person. Islamic philosophy has a scope that is studied and is closely related to Greek philosophy.